Toxicological effects of prolonged exposure of soot-polluted air on some haematological and biochemical parameters of residents of Port Harcourt - Elechi-Amadi, Kemzi; Peace, Batubo Nimisoere; Opusunju, Boma Harris; Jiala, Andrew (International Journal of Research in Medical Sciences, 2019)
Background: Soot is a by-product of incomplete combustion of carbon derived from substances that contains carbon like hydrocarbons, which is associated with various human diseases. The objectives of the studies are to evaluate the toxicological effects of prolonged exposure of soot polluted air on some haematological and biochemical parameters. Methods: One hundred apparently healthy residents of Port Harcourt residing in soot polluted environment for a minimum of 12 months and one hundred apparently healthy subjects residing in non-soot polluted environment outside Port Harcourt were recruited for this study. 5ml of venous blood was collected from each subject after 10hours of overnight fast to estimate the PCV, Hb, RBC, WBC, lymphocytes, neutrophils, bicarbonate, total cholesterol, triglyceride, low density lipoprotein and high density lipoprotein using automated autoanalyzer. Results: There was a statistically significant decrease in the PCV, Hb, RBC and increase in WBC, Lymphocytes and neutrophils. There was also a significant increase in the bicarbonate, total cholesterol and LDL with a decrease in HDL cholesterol as compared to the control. Conclusions: It is concluded that prolong exposure to soot polluted air is harmful and associated with deterioration of haematological parameters and also induces oxidative stress and lipid peroxidation which may increase morbidity and mortality.